Pengembangan Model Inovasi Pembelajaran Berbasis Research and Development di SMP N 3 Pasaman Barat - Wulandari, Ratih; Dwi Amiza, Indah Putri; Annas, Firdaus (Yayasan Lembaga Studi Makwa, 2024)
This research aims to develop a Research and Development (R&D) based learning innovation model at SMP N 3 Pasaman Barat to improve the quality of learning processes and outcomes. Effective learning in junior high schools requires innovative approaches to respond to various educational challenges, such as students' low interest in learning and the limitations of the methods applied. The R&D method is used in this research to design, test and evaluate learning models that suit student characteristics and applicable curriculum needs. The research process includes the needs analysis stage, learning model design, classroom testing, and evaluation of the implementation of the model developed. The research results show that the implementation of the R&D-based learning innovation model at SMP N 3 Pasaman Barat can increase student involvement, improve understanding of teaching material, and significantly improve student learning outcomes. This research concludes that the use of an R&D-based learning model makes a positive contribution to the quality of education at SMP N 3 Pasaman Barat and can be used as a reference for developing learning in other schools. Abstract This research aims to develop a Research and Development (R&D) based learning innovation model at SMP N 3 Pasaman Barat to improve the quality of learning processes and outcomes. Effective learning in junior high schools requires innovative approaches to respond to various educational challenges, such as students' low interest in learning and the limitations of the methods applied. The R&D method is used in this research to design, test and evaluate learning models that suit student characteristics and applicable curriculum needs. The research process includes the needs analysis stage, learning model design, classroom testing, and evaluation of the implementation of the model developed. The research results show that the implementation of the R&D-based learning innovation model at SMP N 3 Pasaman Barat can increase student involvement, improve understanding of teaching material, and significantly improve student learning outcomes. This research concludes that the use of an R&D-based learning model makes a positive contribution to the quality of education at SMP N 3 Pasaman Barat and can be used as a reference for developing learning in other schools.